Reasons for Wives’ Refusal to Fulfill Their Husbands’ Biological Needs in Awangpone Subdistrict: Perspectives from Islamic Law and Positive Law: bahasa inggris - Widia Astuti; Syahabuddin; Ruslan; Nursyirwan; Widya Astika Putri (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2026)
This study aims to analyze the factors causing wives to refuse their husbands' requests for marital sex in Bone Regency and to examine this phenomenon from the perspectives of Islamic and positive law. The novelty of this research lies in its integrative approach, combining empirical societal findings with the normative analysis of both legal frameworks regarding marital obligations. Utilizing a qualitative method, this study employs case study, normative-legal, empirical-legal, and normative-theological approaches. Data were gathered through interviews with married couples in Cakke Bone Village, the village head, the head of the Awangpone Religious Affairs Office, and the registrar of the Watampone Class IA Religious Court. The results indicate that wives' sexual refusal stems from laziness, exhaustion from domestic chores, work fatigue, drowsiness, contraceptive side effects, age, length of marriage, and arranged marriage. Husbands reacted with anger, disappointment, resentment, silence, distancing, or patience. From an Islamic law perspective, such refusals without valid sharia-compliant reasons (such as menstruation, postpartum, or illness) constitute nusyūz. Meanwhile, under positive law, this refusal disrupts marital rights and obligations, potentially serving as grounds for divorce.